War-related trauma and post-traumatic stress disorder prevalence among Syrian university students - Latifeh Yousef; Omar Ebrahim; Mohammad Hareth AlNahr; Fatema Mohsen; Nazir Ibrahim; Bisher Sawaf (European Journal of Psychotraumatology, 2021)
Background: Posttraumatic stress disorder (PTSD) is one of the most prevalent mental disorders in war-affected regions. Syria has endured 9 years of war and yet little is known about the impact of the conflict on the well-being of Syrians who remain. In this study, we investigated trauma and estimated PTSD prevalence among university students in Deir-ez-Zor, a Syrian governorate that was under the siege by ISIS for over 3 years. Methods: A descriptive cross-sectional study design was used on a sample of Al-Furat university students in Deir-ez-Zor. We collected data on socio-demographics, trauma exposure, and stress levels. PTSD Checklist for DSM-5 was used to provide prevalence rate estimates, and determine the symptom severity among Syrian university students. Binary logistic regression was used to identify factors associated with the development of PTSD symptoms. Results: A total of 833 students were recruited into the study, 86.4% of the participants were exposed to at least one traumatic event. The estimated PTSD prevalence was 28.2%, and the highest PTSD rates were found among students who were forced into sexual act (46.3%). A significant association was found between PTSD and internal displacement (p = .032), academic year (p = .002), and social economic status (p = .000). Binary logistic regression indicated that PTSD symptoms were predicted by smoking and third-year university students. Conclusions: The results presented in this research revealed a high prevalence of trauma exposure and PTSD symptoms among a sample of university students in Deir-ez-Zor. These findings call for immediate actions to help the affected population in restoring their mental health, so they can be prepared to face the challenges and demands of the post-conflict period.